The SMU English Teachers' Competence in Developing the Teaching Materials and Strategies According to the 1994 English Syllabus - Ignatius Harjanto (Universitas Negeri Malang, 2016)
The 1994 English syllabus has long been implemented at schools. However, information on how far the implementation of the syllabus has been successful is not sufficiently available. The writer thinks information about the implementation of the syllabus is necessary to guaranttee success of the teaching English at school. This study explores the SMU English teachers' competence in developing the teaching materials and strategies according to the 1994 English syllabus. It is affirmed that teaching materials and strategies are crucial in the learning teaching process and are not separable from the syllabus